New syllabus primary Mathematics workbook 5B - Yee , Foong Pui; Brandon Oh; Lim Li Gek Pearlyn (Karachi : Oxford university press, 2019)
The New Syllabus Primary Mathematics Workbook 5B is designed for students in Primary 5, typically around the age of 10 or 11. It aligns with the Singapore Math curriculum and focuses on consolidating and enhancing key mathematical concepts. Here's a brief summary of the topics usually covered in Workbook 5B: 1-Fractions 2-Decimals 3- Percentage 4-Ratio and Proportion 5-Measurement 6- Geometry 7-Data Handling 8-Word Problems
Keywords: Mathematics workbook 5B; Oxford Mathematics workbook 5B